2001
DOI: 10.1007/s005950170198
|View full text |Cite
|
Sign up to set email alerts
|

Kupffer Cell Function in Ischemic and Nonischemic Livers After Hepatic Partial Ischemia/Reperfusion

Abstract: Hepatic partial ischemic/reperfusion (I/R) injury, in which ischemic and nonischemic areas of the liver are likely to respond to each other after reperfusion, often occurs following hepatobiliary surgical procedures. Kupffer cells (KCs) are considered to play a major role in hepatic I/R injury. To study the activation of KCs in ischemic and nonischemic liver tissues following hepatic I/R, we investigated the superoxide generation and proinflammatory cytokine production of KCs in both liver parts in a rat model… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
18
0

Year Published

2002
2002
2018
2018

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(18 citation statements)
references
References 32 publications
0
18
0
Order By: Relevance
“…Soon after, they mediate the activation of platelet adhesion and neutrophil inflammatory response that infiltrates the injured liver and increases the expression of more adhesion molecules on endothelial cells and more generation of reactive oxygen radicals. The methods by which ischemia/reperfusion injury can be diagnosed include ASGP-R ligand on hepatocytes, showing ischemic damage histologically, hepatobiliary scintigraphy, an easy method in clinics, and electron microscopy, the diagnostic gold standard [135][136][137][138][139][140][141][142][143][144][145]. Reactive oxygen radical scavengers can be used to protect ischemia/reperfusion injury syndrome.…”
Section: Supportive Care For Keeping the Regenerated Liver Functionalmentioning
confidence: 99%
“…Soon after, they mediate the activation of platelet adhesion and neutrophil inflammatory response that infiltrates the injured liver and increases the expression of more adhesion molecules on endothelial cells and more generation of reactive oxygen radicals. The methods by which ischemia/reperfusion injury can be diagnosed include ASGP-R ligand on hepatocytes, showing ischemic damage histologically, hepatobiliary scintigraphy, an easy method in clinics, and electron microscopy, the diagnostic gold standard [135][136][137][138][139][140][141][142][143][144][145]. Reactive oxygen radical scavengers can be used to protect ischemia/reperfusion injury syndrome.…”
Section: Supportive Care For Keeping the Regenerated Liver Functionalmentioning
confidence: 99%
“…1,2 Early activation of Kupffer cells enhances the formation of reactive oxygen species and proinflammatory mediators such as tumor necrosis factor-α, interleukin-1, and proteases. 3 The inhibitory effect of gadolinium chloride (GdCl 3 ) against Kupffer cell activation shows potential as a protective intervention in rat models of in vivo hepatic reperfusion injury and isolated perfused livers. [4][5][6][7][8][9][10] It has also been shown that giving GdCl 3 for liver I/R injury decreases the mortality rate, 11 attenuates neutrophil infiltration and decreases myeloperoxidase activity, 12 improves hepatic function, 5,13 reduces platelet accumulation in cold perfused livers, and prevents apoptosis of sinusoidal endothelial cells.…”
Section: Introductionmentioning
confidence: 99%
“…Hepatic I/R has been shown to generate oxygenderived free radicals by activated Kupffer cells [6,26,27]. A chain reaction of lipid peroxidation initiated by oxygen-derived free radicals compromises cellular viability and ultimately results in tissue injury [28].…”
Section: Discussionmentioning
confidence: 99%